2000
DOI: 10.1089/08892220050193326
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Determinants of Bovine Leukemia Virus Pathogenesis

Abstract: The understanding of HTLV-induced disease is hampered by the lack of a suitable animal model allowing the study of both viral replication and leukemogenesis in vivo. Although valuable information has been obtained in different species, such as rabbits, mice, rats, and monkeys, none of these systems was able to conciliate topics as different as viral infectivity, propagation within the host, and generation of leukemic cells. An alternate strategy is based on the understanding of diseases induced by viruses clos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
79
0
4

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(84 citation statements)
references
References 51 publications
1
79
0
4
Order By: Relevance
“…However, controversy exists regarding the reproducibility of the viral infection in rats (Ibrahim et al, 1994). Bovine leukemia virus (BLV) infection of sheep offers a reliable model of disease associated with deltaretrovirus infections and insight into viral genetic determinants of tumor induction (Willems et al, 2000). This review will focus on current progress in the development of animal models of HTLV-1 infection and transformation.…”
Section: Introductionmentioning
confidence: 99%
“…However, controversy exists regarding the reproducibility of the viral infection in rats (Ibrahim et al, 1994). Bovine leukemia virus (BLV) infection of sheep offers a reliable model of disease associated with deltaretrovirus infections and insight into viral genetic determinants of tumor induction (Willems et al, 2000). This review will focus on current progress in the development of animal models of HTLV-1 infection and transformation.…”
Section: Introductionmentioning
confidence: 99%
“…Bovine leukemia virus (BLV) 1 is a B-lymphotropic retrovirus associated with enzootic bovine leukosis, a disease characterized by an increased number of B-lymphocytes and, in some cases, after a long latency period, by the subsequent development of B-cell leukemia or lymphosarcoma (1). BLV is closely related structurally and biologically to the human T-lymphotropic viruses HTLV-I and HTLV-II (1).…”
mentioning
confidence: 99%
“…BLV is closely related structurally and biologically to the human T-lymphotropic viruses HTLV-I and HTLV-II (1). Expression of BLV is regulated at the transcriptional level by the virus-encoded transactivator Tax BLV (2,3).…”
mentioning
confidence: 99%
“…1,75 The p13 II -Ras signaling connection is further substantiated by studies which revealed interesting analogies and differences between p13 II and the G4 protein of bovine leukemia virus, an oncogenic deltaretrovirus of cattle that is related to HTLV-1. 76 Oncogenic conversion assays showed that G4 cooperates with H-Ras to transform primary rat embryo fibroblasts (REF). 53 In contrast, p13 II was found to inhibit transformation of REF by c-Myc plus H-Ras, significantly reducing both tumor incidence and growth rate.…”
Section: The Impact Of P13 II On Cell Growth and Deathmentioning
confidence: 99%